Salvage reirradiation for local failure of prostate cancer after curative radiation therapy: Association of rectal toxicity with dose distribution and normal-tissue complication probability models - Giovanna Dipasquale, MS; Thomas Zilli, MD; Claudio Fiorino, PhD; Michel Rouzaud, MS; Raymond Miralbell, MD (Advances in Radiation Oncology, 2018)
Purpose: This study aimed to assess the impact of radiation dose on rectal toxicity after salvage external beam radiation therapy (EBRT) with or without a brachytherapy boost for exclusive local failures after the primary EBRT for prostate cancer. Methods and materials: Fourteen patients with no severe residual late toxicity after primary EBRT ± brachytherapy were reirradiated after a median time interval of 6.1 years. The median normalized total dose in 2 Gy fractions (NTD2Gy, α/β ratio = 1.5 Gy for prostate cancer cells) was 74 Gy at primary EBRT and 85.1 Gy at reirradiation. Rectal dose-volume histograms (converted to NTD2Gy_alpha/beta = 3 Gy) and the corresponding normal-tissue complication probability (NTCP) values for gastrointestinal (GI) toxicity were evaluated for 2 groups: High GI toxicity (grade ≥3) and low GI toxicity (grade ≤2). Results: The 5-year grade ≥3 GI toxicity-free survival rate was 57.1%. The median rectal V70Gy and maximum dose to 1 cm3 (D1ccrect) at primary EBRT were both predictive for grade ≥3 GI toxicity (9% vs 0%; P = .04 and 72.2 Gy vs 66.8 Gy; P < .01, respectively). When adding primary radiation therapy (RT) and reirradiation plans, the median D1ccrect was 139.8 Gy versus 126.7 Gy (P < .01) for high and low GI toxicity groups. NTCP >10% at primary RT was predictive for high GI toxicity at reirradiation (P < .05). Conclusions: Even in the absence of residual toxicity after primary RT, rectal doses >70 Gy and NTCP >10% calculated for a first irradiation may be associated with a higher risk of developing high GI toxicity at reirradiation with a possible D1ccrect threshold of 130 Gy.